INTERACTIVE METHODS FOR TEACHING ENGLISH SPEAKING TO KIDS - Sevarakhon Dekhkonova (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
This article explores interactive methods for teaching English speaking skills to children learning English as a second language (ESL). Emphasizing dynamic and engaging approaches, the strategies discussed aim to foster effective communication in young learners. By creating supportive learning environments and integrating interactive activities, educators can enhance language acquisition while making the learning process enjoyable and memorable for children. Practical insights and activities tailored to ESL contexts are highlighted to help educators cultivate speaking proficiency from an early age.